(untitled) - Boerlage, Annette S. (Wednesday, 2013)
This thesis combines experiments, statistical analysis and mathematical modelling of FZT in aquaculture to improve understanding of the impact of several control measures. This first chapter is an introduction on FZTs in general, FZTs in Vietnam, FZTs in aquaculture, control measures against FZTs in humans and control measures against FZTs on aquaculture farms.
Keywords: Nuôi trồng thủy sản,Aquaculture